THE FEATURES AND TYPES OF MULTIMEDIA TECHNOLOGIES - Yorkulova Marjona Shukhratovna; Akhmedova Malohat Ergashevna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article is about the features and types of multimedia technologies.